Integrasi Sistem ERP, Arus Informasi Dan Kualitas Informasi - Muhammad Nawawi; Edward Fazri (Universitas Muhammadiyah Malang, 2022)
This paper aims to provide empirical evidence regarding the relationship between the level of integration of ERP systems and the quality of information perceived by managers directly and indirectly. The quality of information is affected by the presence of specific features of information flow, defined as information processing capacity, meeting intensity, and information sharing. This research was conducted by approaching structural equation modeling (SEM) with a test tool using partial least square (PLS). Empirical results show that the level of integration of ERP systems has a positive effect on information flow variables and information flow positively affects the quality of information. Other results also show that the level of integration of ERP systems can positively and indirectly affect the quality of information obtained by managers mediated by the flow of information. Managers can benefit from this research in supporting decision making to achieve the optimal level of integration of ERP systems used to improve the quality of information within the company.